Kamusi ya fasihi : istilahi na nadharia - Wamitila, K. W. (Nairobi, Kenya : Focus Books, 2003)
A dictionary of literature: terms and concepts.
Includes bibliographical references (p. 385-389).
In Swahili.
Keywords: Swahili language -- Terms and phrases; Swahili literature -- Terminology